PERAN SISTEM INFORMASI AKUNTANSI DALAM PEMANFAATAN TEKNOLOGI TERHADAP PEMBUKUAN DIGITAL PADA UMKM - Ari Rohmana; Hwihanus Hwihanus (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Writing this article aims to find out the use of technology, especially in the field of accounting, to know the role of accounting information systems in SME, and the application of digital bookkeeping to SME. The method used is a case study method using related journals. The results that have been obtained indicate that the current use of technology in SME has implemented digitalization in their activities. For example on sales and payments. However, many SME bookkeepers still use bookkeeping manually using paper. Counseling is carried out, it is hoped that with the rapid advancement of technology, currently SME actors can carry out bookkeeping in their businesses effectively and efficiently so that they can create technologically literate SME.